2012
DOI: 10.1007/s10508-012-9935-5
|View full text |Cite
|
Sign up to set email alerts
|

Who, What, Where, When (and Maybe Even Why)? How the Experience of Sexual Reward Connects Sexual Desire, Preference, and Performance

Abstract: Although sexual behavior is controlled by hormonal and neurochemical actions in the brain, sexual experience induces a degree of plasticity that allows animals to form instrumental and Pavlovian associations that predict sexual outcomes, thereby directing the strength of sexual responding. This review describes how experience with sexual reward strengthens the development of sexual behavior and induces sexually-conditioned place and partner preferences in rats. In both male and female rats, early sexual experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
178
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 193 publications
(189 citation statements)
references
References 248 publications
1
178
1
Order By: Relevance
“…In flies, the function of dopaminergic neurons has been implicated in responses to both rewarding and aversive stimuli (16)(17)(18)(19), making it a candidate neuromodulator to signal the beneficial and detrimental effects of ethanol. Dopamine signaling has also been implicated in other innate behaviors required for survival, such as food consumption, sex, and social interaction (20)(21)(22). Although the circuitry for ethanol oviposition preference is unknown, both dopaminergic and mushroom body (MB) signaling is required for flies to remember ethanol as a reward (23).…”
mentioning
confidence: 99%
“…In flies, the function of dopaminergic neurons has been implicated in responses to both rewarding and aversive stimuli (16)(17)(18)(19), making it a candidate neuromodulator to signal the beneficial and detrimental effects of ethanol. Dopamine signaling has also been implicated in other innate behaviors required for survival, such as food consumption, sex, and social interaction (20)(21)(22). Although the circuitry for ethanol oviposition preference is unknown, both dopaminergic and mushroom body (MB) signaling is required for flies to remember ethanol as a reward (23).…”
mentioning
confidence: 99%
“…Interface between the medial preoptic area and nucleus accumbens have also been documented (Balfour et al, 2004;Everitt, 1990;Pfaus et al, 2012).…”
Section: Androgen and Estrogenmentioning
confidence: 93%
“…The medial preoptic area is more of a center that coordinates the internal state with external contingencies. In general, dopamine within the medial preoptic area is critical for solicitations in females (Graham and Pfaus, 2010;Pfaus et al, 2012). As summarized below, many studies have reported involvement of the nucleus accumbens in the regulation of sexual motivation.…”
Section: Androgen and Estrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…When copulation occurs, the female rat is prepared not only to accept the male and receive sexual stimulation (clitoral and vaginocervical), but also her brain is in a hormonal state that facilitates learning. The effect of hormones, and sexual stimulation are required for female rats to develop conditioned partner preferences triggered by sexual stimuli (Parada et al, 2010;Corona et al, 2011;Parada et al, 2011;Pfaus et al, 2012).…”
Section: Natural Stimuli For Intraspecific Attachmentmentioning
confidence: 99%